BUKU CERITA BERBASIS POWER POINT SEBAGAI PENGENALAN EKOLITERASI PADA ANAK USIA 5 SAMPAI 6 TAHUN - Ismawati, Dwi; Putra, Ari; Palenti, Citra Dwi; Gusti, Ririn; Afrodita, Meli; Sari, Dwi Lyna (Jurnal Pendidikan Luar Sekolah, 2023)
Abstract This study aims to design and develop story books based on Microsoft Office as an introduction to ecoliteracy in children aged 5-6 years. This study adopts the ADDIE design and development model. Data collection techniques using storytelling tests, questionnaires, and interviews. Expert assessment involved media experts, material experts, and PAUD teachers to assess a prototype for developing Microsoft Office-based storybooks as an introduction to ecoliteracy in children aged 5-6 years. Storytelling tests and interviews were used in the piloting process. Quantitative data were obtained from pretest and posttest scores and questionnaires for expert validation. Descriptive qualitative data analysis techniques were used to process interview data. Quantitative data analysis was used to test the scores obtained from the pre and post-test. This research produces (1) story books based on Microsoft Office as an introduction to ecoliteracy in children aged 5-6 years and (b) products that have been tested for effectiveness in improving children's ecoliteracy abilities and some of the implications and recommendations are also discussed. Abstrak Penelitian ini bertujuan untuk merancang dan mengembangkan buku cerita berbasis Microsoft Office sebagai pengenalan ecoliteracy pada anak usia 5-6 tahun. Penelitian ini mengadopsi model desain dan pengembangan ADDIE. Teknik pengumpulan data menggunakan tes bercerita, kuisioner, dan wawancara. Penilaian ahli melibatkan ahli media, ahli materi, dan guru PAUD untuk menilai prototipe mengembangkan buku cerita berbasis Microsoft Office sebagai pengenalan ecoliteracy pada anak usia 5-6 tahun. Tes bercerita, dan wawancara digunakan dalam proses uji coba. Data kuantitatif diperoleh dari nilai pretest dan posttest serta angket untuk validasi ahli. Teknik analisis data kualitatif deskriptif digunakan untuk mengolah data wawancara. Analisis data kuantitatif digunakan untuk menguji skor yang diperoleh dari pre dan post-test. Penelitian ini menghasilkan (1) buku cerita berbasis Microsoft Office sebagai pengenalan ecoliteracy pada anak usia 5-6 tahun dan (b) produk yang telah teruji efektivitas, dalam meningkatkan kemampuan ecoliteracy anak dan beberapa implikasi dan rekomendasi juga dibahas.